C4: An Interdisciplinary Approach to Improving Retention with Developmental Students - Kirk Weller; Heather Pavletic (Academic Chairpersons Conference Proceedings, 2020)
In this session, we describe an interdisciplinary learning community program designed to improve retention among freshman students with three developmental placements. We will discuss how a similar program could be developed at other institutions and emphasize issues of transferability and scalability in the context of declining resources and retention.
Keywords: developmental education; retention; interdisciplinary programming; learning communities; professional mindset